Analisis Keberlanjutan Usaha Peternakan Ayam Broiler yang Bermitra dengan PT Charoen Pokphand Jaya Farm di Kecamatan Tapung Kabupaten Kampar - Tua, Diah Uli; Cepriadi, Cepriadi; Herlon, Meki (Universitas Galuh, 2025)
Broiler chicken farming has great potential to be developed as a source of animal protein that is increasingly needed along with population growth. The increasing demand for broiler chicken meat requires sustainable business management from various aspects, including economic, ecological, social, technological, and partnership. However, this business still faces a number of challenges, such as inefficient waste management, limited use of technology, and suboptimal partnership patterns. This study aims to analyze the level of sustainability of broiler chicken farming businesses and identify sensitive attributes that affect the sustainability of these livestock businesses. This study involved 5 farmer respondents who were selected by purposive sampling based on three criteria, namely farms that partner with PT. Charoen Pokphand, farmer locations in Tapung District, and have harvested at least the last five periods. Primary data were collected through in-depth interviews using questionnaires and secondary data were obtained through various related agencies and the internet. Data analysis was carried out using Multidimensional Scaling (MDS) with the Rapfish approach and Leverage Analysis to determine the attributes that most influence sustainability. The results of the study indicate that overall, broiler chicken farming in Tapung District is quite sustainable based on the five dimensions analyzed, although there are still dimensions that need to be improved to achieve a better status. Sensitive attributes that most affect business sustainability include the percentage of chicken deaths, farmer income levels, waste management, technology adoption, and the effectiveness of partnership patterns. Therefore, it is necessary to increase the capacity of farmers in waste management, utilization of modern technology, and strengthening partnership patterns so that the sustainability of broiler chicken farming businesses can continue to be improved in the future.